Tax policy and OECD unemployment - Alvin Ó. Murchú (University College Dublin, Department of Economics, 2002)
The effect of changes in payroll taxes on wages is a question of tax incidence. If workers can shift the burden of taxation onto employers, in the form of higher wages, we may expect increases in unemployment. This paper examines the extent to which workers succeed in shifting the burden of taxation onto employers and therefore the effects on unemployment of higher direct taxes. A reduced form vector autoregression model is used to estimate the effects, of a shock to direct taxes, on both wages and unemployment. The empirical estimates, estimated separately for eleven OECD countries, show workers failing to shift the burden of higher taxes and consequently insignificant changes in unemployment.
hdl:10197/1276
Keywords: 330; Lohnsummensteuer; Personalzusatzkosten; Arbeitslosigkeit; OECD-Staaten